2016
DOI: 10.3389/fphys.2016.00581
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mechanisms of Exercise-Induced Hypoalgesia Using Somatosensory and Laser Evoked Potentials

Abstract: Exercise-induced hypoalgesia is well described, but the underlying mechanisms are unclear. The aim of this study was to examine the effect of exercise on somatosensory evoked potentials, laser evoked potentials, pressure pain thresholds and heat pain thresholds. These were recorded before and after 3-min of isometric elbow flexion exercise at 40% of the participant's maximal voluntary force, or an equivalent period of rest. Exercise-induced hypoalgesia was confirmed in two experiments (Experiment 1–SEPs; Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 87 publications
4
32
1
Order By: Relevance
“…The perceived pain intensity of a suprathreshold stimulus is consistently reduced by aerobic, isometric, and dynamic resistance exercises, 42 , 64 , 98 and acute exercise can reduce ratings of pain unpleasantness even in the absence of a change in pain intensity. 80 In addition, low-intensity nonpainful aerobic and isometric exercises also increase the tolerance to a painful stimulus. A 20% increase in pain tolerance was observed by Vaegter et al 199 after a 3-minute submaximal isometric knee extension exercise, and after a 6-minute walking exercise 73 compared with rest in 35 pain-free individuals.…”
Section: Pain Outcomes After Acute and Regular Exercise In Pain-frmentioning
confidence: 99%
See 2 more Smart Citations
“…The perceived pain intensity of a suprathreshold stimulus is consistently reduced by aerobic, isometric, and dynamic resistance exercises, 42 , 64 , 98 and acute exercise can reduce ratings of pain unpleasantness even in the absence of a change in pain intensity. 80 In addition, low-intensity nonpainful aerobic and isometric exercises also increase the tolerance to a painful stimulus. A 20% increase in pain tolerance was observed by Vaegter et al 199 after a 3-minute submaximal isometric knee extension exercise, and after a 6-minute walking exercise 73 compared with rest in 35 pain-free individuals.…”
Section: Pain Outcomes After Acute and Regular Exercise In Pain-frmentioning
confidence: 99%
“… 130 Controlled studies using similar methodology but different designs (eg, crossover trials and parallel trials) have also been conducted. 80 , 162 , 195 , 204 The results of these studies, especially those where participants were randomized to exercise or control, or where the order of exercise and control were randomized and counterbalanced for crossover trials, give a less biased estimate of the effect of a single bout of exercise on pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pain-free individuals, acute exercise can transiently reduce pain sensitivity, known as exerciseinduced hypoalgesia (EIH) [2]. EIH is often reported when assessed at non-exercising muscles, but greater increases in pressure pain thresholds (PPTs) are seen at the exercising muscles [3][4][5][6][7]. This suggests that EIH involves -in addition to peripheral or segmental pain modulatory processes -a systemic component of central descending inhibition, which is reflected in EIH effects at non-exercising muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that exercise can induce hypoalgesia by peripherally modulating the transduction, transmission, and processing of noxious stimuli (Jones, Taylor, Booth, & Barry, 2016). Some other hypotheses include the systemic activation of the endogenous opioid, serotoninergic and immune system, and the central activation of the corticothalamic descending inhibitory pathways (K. F. Koltyn, 2000), assuming that these physiological mechanisms could be assessed by quantitative sensory testing, such as paint threshold (PT).…”
Section: Introductionmentioning
confidence: 99%